Work Motivation of Employees in the Palu City Religious Court Office, Central Sulawesi Province - Abu Rizal Bakri; Mustainah Mustainah; Shadiq Shadiq (Universitas Negeri Makassar, 2019)
Employees are one of the components that determine and play an important role in the achievement of an work effectiveness in an organization. The purpose of this study is to determine the work motivation of employees at the Religious Court Office in Palu, Central Sulawesi Province, the type of research used is descriptive. While the basic research is qualitative. The number of informants in this study were 5 (five) people. Data collection techniques carried out in 3 (three) ways, namely observation, interviews and documentation. This study uses the theory of Frederick Herzberg, where there are 11 (eleven) aspects studied, namely achievement, appreciation, responsibility, opportunities for advancement, work itself, physical working conditions, interpersonal relations, company policy and administration, supervision, salary, and job security. Research conducted by researchers, obtained the conclusion that the work motivation contained in each employee is good enough, but from every aspect there is not everything can work well in every employee of the Palu City Religious Court, thus affecting the level of motivation in each employee existing and resulting in less than the maximum work activities.